Early Buddhism as Philosophy of Existence: Freedom and Death - Babbitt, Susan E. (Anthem Press, 2022)
This book makes the connection between early Buddhism and nature. Early Buddhism was a system of thinking which applied the universal laws of nature to human beings. It was a comprehensive worldview. But after the first 400 to 500 years, it was mostly lost.